The Judge’s Ratio Decidendi in The Annulment of a Deed of Sale and Purchase Executed by a Land Deed Official (PPAT) (Review of Judgment No. 80/Pdt.G/2020/PN.Btl) - Alya Zharifa Rahmadhani; Noor Saptanti; Bambang Manumayoso (International Journal of Educational Research & Social Sciences, 2026)
This study aims to examine and understand the legal principles applied by the judge in the annulment of a Deed of Sale and Purchase executed by a Land Deed Officer (PPAT) in Judgment No. 80/Pdt.G/2020/PN.Btl. The type of research used in this study is normative legal research, which involves examining legal materials derived from various laws and regulations as well as other materials from the literature. This legal writing employs both the statutory approach and the conceptual approach. The legal materials used in this normative legal study consist of primary and secondary legal sources. The method of collecting legal materials involves a literature review, which is conducted by reading and citing books, as well as analyzing laws and regulations, documents, and information relevant to the research being conducted. The research analysis was conducted using descriptive analysis. Research findings indicate that judges who tend to apply the theory of responsive law do not merely focus on the formal validity of authentic documents (legal positivism), but actively respond to the public’s sense of justice and the social realities surrounding the case. The ruling invalidating the deed took effect when the judge prioritized substantive justice and granted legal protection to the plaintiffs as parties acting in good faith.